Assessments of maternal psychosocial adaptation for pre-labor hospitalized pregnant women in Japan - Yasuka Nakamura; Toyoko Yoshizawa; Fumi Atogami (MDPI AG, 2011)
Maternal psychosocial adaptation to pregnancy is significant task for women during pregnancy. Antepartum hospitalization is often characterized by maternal anxiety, boredom, feelings of imprisonment, and loneliness. The purpose of this study was to explore maternal psychosocial adaptation during pregnancy for hospitalized pregnant women compared with such adaptation in low-risk pregnant women from a reference population. This was a cross-sectional study with convenience samples of high-risk hospitalized and low-risk mothers. This study was carried out in five hospitals and two clinics between March and December 2009 in several areas of Japan. Subjects were 189 hospitalized women diagnosed with premature labor who had received continuous 24-h treatment with intravenous ritodrine hydrochloride for more than 1 week. The Japanese version of Prenatal Self-Evaluation Questionnaire was administered to measure maternal psychosocial adaptation during pregnancy. Women in hospitalized group had significantly lower adaptation in acceptance of pregnancy and preparation for labor (P<.05-.001) and showed significantly higher adaptation in identification of a motherhood role and relationship with her husband. Moreover, in hospitalized group, relationship with her husband showed significantly higher adaptation (P<.05) in primipara, acceptance of pregnancy and preparation for labor were significantly lower adaptation score (P<.01-.001) in multipara. Hospitalized pre-term pregnant women should be assessed maternal psychosocial adaptation especially the domains of acceptance of pregnancy, preparation for labor, relationship with her husband, and identification of a motherhood role. Health care provider should know the character and background of those women as well as the character of primipara and multipara.